2020
DOI: 10.1002/adhm.201901255
|View full text |Cite
|
Sign up to set email alerts
|

Biofabrication Strategies and Engineered In Vitro Systems for Vascular Mechanobiology

Abstract: The vascular system is integral for maintaining organ‐specific functions and homeostasis. Dysregulation in vascular architecture and function can lead to various chronic or acute disorders. Investigation of the role of the vascular system in health and disease has been accelerated through the development of tissue‐engineered constructs and microphysiological on‐chip platforms. These in vitro systems permit studies of biochemical regulation of vascular networks and parenchymal tissue and provide mechanistic ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 538 publications
(858 reference statements)
0
29
0
Order By: Relevance
“…The technology has grown and upgraded from the study of cell adhesion properties and dynamics into the development of tissue-on-a-chip and later into organ-on-a-chip for biochemical and pathological studies. The monolayer of cells was grown in the microfluidic channel to mimic the human vascular system, and it can be used for bioengineering and biochemical analysis [ 101 ]. Basabe-Desmonts et al reported a simple method, interfacial platelet cytometry (iPC) platform with a self-powered microfluidic device enabling platelet separation, and its adhesion studies [ 102 ].…”
Section: Single-cell Mechanical Properties For Mechanotransductionmentioning
confidence: 99%
“…The technology has grown and upgraded from the study of cell adhesion properties and dynamics into the development of tissue-on-a-chip and later into organ-on-a-chip for biochemical and pathological studies. The monolayer of cells was grown in the microfluidic channel to mimic the human vascular system, and it can be used for bioengineering and biochemical analysis [ 101 ]. Basabe-Desmonts et al reported a simple method, interfacial platelet cytometry (iPC) platform with a self-powered microfluidic device enabling platelet separation, and its adhesion studies [ 102 ].…”
Section: Single-cell Mechanical Properties For Mechanotransductionmentioning
confidence: 99%
“…[ 61 ] Laser ablation has also been explored as a method for generating highly accurate and precise vascular networks within hydrogels through the degradation of the hydrogel with a pulsed laser on an image‐guided control system, so that cells can then be seeded in the newly formed channels. [ 182,183 ] These strategies for engineering vasculature for in vitro studies and implantations, along with several others, are discussed in detail in recently published reviews by Vunjak‐Novakoiv and co‐workers [ 184 ] and Slater co‐workers [ 185 ]…”
Section: Tools and Techniques To Investigate Nanoparticle Transport Pmentioning
confidence: 99%
“…The pulsatile nature of blood flow exposes vascular cells to cyclic tensile strain which can be uniaxial or multiaxial, depending on the blood vessel location. [ 118 ] Applying cyclic stretch in the physiological regime (5–10%) can significantly enhance proangiogenic GF secretion, microvessel sprouting, and lumen orientation. [ 119 ] In addition, the degree of cell‐induced forces directly correlates not only with vessel elongation but with network quality as well.…”
Section: Meso‐ and Microvascular Engineeringmentioning
confidence: 99%